Unraveling the potential of bacteria isolated from the equatorial region of Indian Ocean in mercury detoxification - Joshi, Gajendra; Verma, Pankaj; Meena, Balakrishnan; Goswami, Prasun; Peter, D Magesh; Jha, Dilip Kumar; Vinithkumar, Nambali Valsalan; Dharani, Gopal (Frontiers in Marine Science, 2022)
The marine environment is the most vital and flexible because of the continual variations in salinity, temperature, and pressure. As a result, bacteria living in such an environment maintain the adaption mechanisms that are inherent in such unstable environmental conditions. The harbouring of metal-resistant genes in marine bacteria contributes to their effectiveness in metal remediation relative to their terrestrial counterparts. A total of four mercury-resistant bacteria (MRB) i.e. NIOT-EQR_J7 (Alcanivorax xenomutans); NIOT-EQR_J248 and NIOT-EQR_J251 (Halomonas sp.); and NIOT-EQR_J258 (Marinobacter hydrocarbonoclasticus) were isolated from the equatorial region of the Indian Ocean (ERIO) and identified by analysing the 16S rDNA gene sequence. The MRBs can reduce up to 70% Hg(II). The mercury (Hg) volatilization was confirmed by the X-ray film method together with amplifying the mercuric reductase (merA) gene. The outcomes obtained from ICP-MS validated that the Halomonas sp. NIOT-EQR_J251 was more proficient in removing the Hg from culture media than other isolates. Fourier transform infrared (FT-IR) spectroscopy results revealed alteration in several functional groups attributing to the Hg tolerance and reduction. The Gas Chromatography-Mass Spectrometry (GC-MS) analysis confirmed that under mercury stress, strain Halomonas sp. (NIOT-EQR_J248 and NIOT-EQR_J251) released Isooctyl thioglycolate (IOTG) compound. The molecular docking results suggested that IOTG can efficiently bind with the glutathione S-transferase (GST) enzyme. A pathway has been predicted based on the GC-MS metabolic profile and molecular docking results, which suggests that the compound IOTG may mediate mercuric reduction via merA-GST related detoxification pathway.